The impact of the environmental protection law issued in 2015 on different types of polluters - Jiayi Liu (Energy Reports, 2022)
In this paper, the data from 2008 to 2020 of enterprises in different types of pollution industries of A-share listed companies in China are selected as samples. Through empirical demonstration, the following conclusions are drawn: First, command-based and market-based environmental regulations can effectively promote enterprises’ green innovation behavior, and command-based environmental regulations have threshold effect. Maximize the effect of green innovation within moderate intensity; otherwise, its output will be inhibited; The effect of public participation environmental regulation is not significant. Second, command-based environmental regulation, market-based environmental regulation and public-participation environmental regulation can effectively promote the improvement of enterprise environmental performance, but the good realization of environmental performance in the early stage has a restraining effect on the current value. Third, different forms of environmental regulation tools both short-term and long-term value of the enterprise has a significant role in promoting, but for the effects of long-term value is greater than the short-term profit, mainly through environmental regulation under the action of enterprise green innovation “innovation” and “first-mover advantage” and “reputation effect” of environmental performance. Fourth, under environmental regulations, enterprises’ regulation rent-seeking behavior is beneficial to enterprises’ short-term environmental performance and economic profit increase, but in the long run, it inhibits enterprises’ green innovation behavior and long-term value growth. Fifthly, by virtue of the information transmission function focused by the media, environmental regulation has a significant promoting effect on enterprises’ green innovation output, environmental performance improvement and long-term value growth, but leads to a downward trend of enterprises’ short-term profits.